1987
DOI: 10.1139/f87-334
|View full text |Cite
|
Sign up to set email alerts
|

An Indirect Rapid Methods Approach to Assessment

Abstract: Strategies and tactics are explored for increasing the usefulness of assessment information obtainable under manpower and budget restrictions. A concept of indirect rapid assessment is gradually emerging based on a collection of rapid methods of varying degrees of accuracy, sophistication, and data requirements. These tactics involve the use of statistics which are functionally related to parameters of interest. Stock composition, growth, mortality, population size, intrinsic rate of increase, and stock produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The life history relationships were derived from regression analysis of walleye life history data reported in Beverton (1987). Natural mortality rates were estimated from longevity values using a relationship between mortality and longevity reported by Hoenig et al (1987).…”
Section: Predictability Of Interpopulation Differences In Life Histormentioning
confidence: 99%
“…The life history relationships were derived from regression analysis of walleye life history data reported in Beverton (1987). Natural mortality rates were estimated from longevity values using a relationship between mortality and longevity reported by Hoenig et al (1987).…”
Section: Predictability Of Interpopulation Differences In Life Histormentioning
confidence: 99%
“…Indirect estimation of population variables and life history parameters is a potential use for con-dition indices. Indirect assessment methods (Hoenig et al 1987) use routinely collected data to estimate data that would be more expensive to collect directly. Given satisfactory models of growth rate based on condition, inexpensive length and weight data might replace more expensive growth or age data.…”
mentioning
confidence: 99%
“…For reference lakes, this was calculated for all possible years from 1995 to 2004 to obtain the maximum number of year-to-year changes. Observed changes in the study lakes were then compared to the percentiles of the reference distribution; changes at extreme ends, or outer quartiles (Hoenig et al 1987, Schupp 1992, of the reference distribution suggested a likely effect due to treatment.…”
Section: Methodsmentioning
confidence: 99%